To apply the Pythagorean theorem, we need to find the distances along the x-axis and y-axis between the two points.
The distance along the x-axis is given by the difference in x-coordinates:
x2 - x1 = -2 - 4 = -6
The distance along the y-axis is given by the difference in y-coordinates:
y2 - y1 = -1 - 2 = -3
Now we can use these distances to apply the Pythagorean theorem and find the length between the two points:
Length = √((-6)^2 + (-3)^2)
= √(36 + 9)
= √45
≈ 6.71 (rounded to the nearest hundredth)
apply the pythagorean theorem to find the length between the two points (4,2) (-2, -1). round your answer to the nearest hundredth if necessary
1 answer